Comerţul cu servicii al ue sub impactul globalizării şi al crizei economice - Agnes Ghibuţiu; Iulia Monica Oehler-Șincai (European Institute of Romania, 2010)
– This paper examines the evolution of the EU's trade in services over the 2004-2008 period in comparison with its trade in goods. It aims to disentangle the main trends shaping the EU's services trade flows under the impact of increasing globalisation and the last two waves of EU enlargement. Relying on BoP trade statistics published by Eurostat and the WTO, it highlights the recent changes in the EU's services flows in terms of dynamics, composition, trade balance as well as patterns of specialisation and integration into the internal and global market. It also reveals the main trends prevailing in the evolution of extra and intra-EU trade flows, and their relevance for the process of economic integration within the EU. The purpose of the paper is to contribute to the discussion of the issues related to services trade in the EU since this topic is focusing to a far lesser extent the attention of current economic literature than trade in goods. Hence, our empirical investigation attempts to find the answers to the following questions: What is the significance of services trade flows for the EU as compared with trade in goods, and which is their role in the global economy? How relevant is trade in services from the perspective of European economic integration? What are the effects of the global financial and economic crisis on the EU's trade in services, and which are its future prospects? Following the answers to these questions, the paper is structured around five sections. The last one summarizes the main findings of the authors.
Keywords: F14; F15; L80; O52; 330; European Union; trade in services; trade in goods; economic integration; global financial and economic crisis; Dienstleistungshandel; Außenhandel mit Industriegütern; Internationale Wirtschaft; Finanzkrise; Wirtschaftskrise; Regionale Wirtschaftsintegration; EU-Staaten